Mistisisme Ekstraversif dalam Teks Panugrahan Dalem - Hari Harsananda (Jurnal Yoga dan Kesehatan, 2021)
Religion is a means for humans to connect with God, this relationship is full of mysticism, both introversive mysticism and extraversive mysticism. The Panugrahan Dalem text is one of the literary texts that contains the teachings of extraversive mysticism, namely the teachings of mysticism "outside" from within which refers to the forces of the universe and so on. The method used in this study uses a qualitative method with a literature study. The implementation of extraversive mysticism in the Panugrahan Dalem text lies in the worship of Sang Hyang Pancamahabhuta which consists of Yeh Nyom or Sang Bhuta Agasati, Getih or Sang Bhuta Mrajapati, placenta or Sang Bhuta Banaspati and Lamad or Vernix Caseosa or Sang Bhuta Banaspatiraja which is related to Kanda Pat teachings through chanting of mantras, the use of both the Wianjana script and the Modre script as well as the use and giving of offerings that function to increase magic and kawisesan. There is also the concept of mantras and scripts that are present as a means for treatment or Usada as the implementation of the Extraversive mysticism teachings.